How and when do firms adjust their investments toward targets? - Catharina Klepsch; Ralf Elsas (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Due to adjustment costs, firms' only partially adjust toward desired investment levels. By exploiting unique survey data on firms' desired investments, we examine how and when firms adjust their investments toward stated plans (targets). More precisely, we examine how financing costs due to asymmetric information, disruption costs, and costs due to asset irreversibility influence firms' adjustment costs and thus adjustment behavior. We find that firms with sufficient cash flows to finance all desired investments adjust significantly faster toward targets than firms with insufficient cash flows. Moreover, firms with either minor investment targets, a large fraction of desired replacement investments or low asset irreversibility adjust within shorter time compared to firms with major investment plans, capacity expansion targets or high asset irreversibility, respectively. Finally, although several prior studies find that the financial crisis of 2008 and 2009 reduced firms' realized investment spending, our results indicate that firms' speed of adjustment toward target investments was not influenced by the crisis.
Keywords: D92; E22; G31; 330